Parent Skills Training Treatment for Parents of Children and Adolescents with Eating Disorders: A Qualitative Study - Goodier, G.; McCormack, J.; Egan, Sarah; Watson, Hunna; Hoiles, Kimberley; Todd, G.; Treasure, J. (John Wiley & Sons, Inc., 2014)
Objective: This study examined the experience of parents of children with eating disorders after having participated in a skills-based training intervention. Method: Eleven parents were interviewed and transcripts were analysed using inductive thematic analysis. Results: Parent responses were organised around key themes of (1) effectiveness and acceptability of the intervention; (2) interpersonal experience of the group process; and (3) feedback on intervention content. Overall, the transfer of specialist skills was highly valued by parents and applied within the home and hospital setting. Discussion: This study contributes preliminary evidence that skills-based training may improve parent self-efficacy, psychological distress, anxiety, and burden. This intervention can also be a cost-effective method for supporting carers, and future research is required to contribute data on treatment efficacy for patients in addition to parents.